1987
DOI: 10.3727/015613887791918042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age of Chicks on Maternal Behaviour in Domestic Hens

Abstract: RICHARD-YRIS, M.A. and G. LEBOUCHER. 1987.Influenceof age of chickson maternal behaviourin domestic hens. Bird Behaviour 7: 82-86. Newlyhatched and eight day-oldchicks induced maternal responses in hens without previousmaternal experience. However, maternal behaviour emerged sooner in hens confined with younger chicks. Replacement of eight or 15 day-old chicks by newly-hatchedones, clearly indicated that all hens, whatever their prior experience, were capable of immediatelyexpressingappropriate maternal respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One possible scenario is that the parental motivation for brooding is governed by a fixed time program and decreases steadily after hatching. However, in disagreement with this hypothesis of a fixed time program for brooding are the observations of Richard- & Leboucher (1987) in the domestic fowl Gallus domesticus. They found that substituting old chicks with younger ones led immediately to the appropriate maternal brooding response.…”
Section: Time Allocationmentioning
confidence: 94%
“…One possible scenario is that the parental motivation for brooding is governed by a fixed time program and decreases steadily after hatching. However, in disagreement with this hypothesis of a fixed time program for brooding are the observations of Richard- & Leboucher (1987) in the domestic fowl Gallus domesticus. They found that substituting old chicks with younger ones led immediately to the appropriate maternal brooding response.…”
Section: Time Allocationmentioning
confidence: 94%
“…In our experiment, flocks of chicks met the robot only 36 h after hatching; hence, conditions for an unconditional attachment were probably not met. However, as late filial attachment of chicks has been reported (Vidal 1976, Richard-Yris andLeboucher 1987b), the question of attachment deserves discussion, especially if robot movement can have a role in this issue (Ten Cate 1986, 1989.…”
Section: Attachment Of Chicks To the Robotmentioning
confidence: 99%